Human Resource Management Strategies to Reduce Burnout and Improve Well-Being: A Literature Review with the Job Demands-Resources Framework - Laelawati, Kania; Pertiwi, Dewi; Fauzi, Haris (Jurnal Economic Resource, 2025)
High rates of emotional exhaustion (burnout) and declining psychological well-being of employees are serious challenges in modern human resource management, especially in sectors with high work pressure. This study aims to examine the effectiveness of integrated human resource management (HRM) strategies in reducing burnout and improving employee psychological well-being through a systematic literature review approach. This study used a qualitative method with a descriptive-analytical approach to more than 30 recent scientific articles, which included meta-analyses, systematic reviews, and empirical studies from various industry sectors. The literature reviewed was selected using a purposive sampling technique based on topic relevance and publication quality. The results showed that a combination of Employee Assistance Programs (EAP), work flexibility, supportive leadership training, and mental well-being programmes were significantly effective in reducing burnout and improving psychological well-being. The effectiveness of the interventions was influenced by organisational contexts such as psychosocial safety climate and transformational leadership style. In addition, technology-based digital approaches were also found to be effective when combined with interpersonal support. These findings provide important implications for the development of wellbeing-based HRM strategies in building psychologically healthy and sustainable workplaces.